Acceptance Measurement of Health Insurance Information System Based on Technology Acceptance Model (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
The objective of this research is to evaluate P-Care BPJS information system based on Technology Acceptance Model (TAM). The type of research is analytical, cross sectional approach. Number of respondents 206 P-Care BPJS users at primary health care. Data analysis using linear regression. Based on correlation test external variables with percieved usefulness, showed high correlation = 0.6 (p 0.001); external variables with percieved ease of use showed moderate correlation = 0.4 (p 0.001); perceived ease of use with attitude showed moderate correlation = 0.5 (p 0.001); percieved usefulness with attitude showed high correlation = 0.7 (p 0.001); perceived usefulness with actual use showed moderate correlation = 0.5 (p 0.001); behavioral intention to use with percieved usefulness showed moderate correlation = 0.5 (p 0.001); attitude with behavioral intention to use showed high correlation = 0.6 (p 0.001); behavioral intention to use with actual use showed high correlation = 0.7 (p 0.001).